The association between cotton bud usage and ear infections among student - Aishwara, R. Naina; Tambunan, Andika Zayani; Lubis, Yuliani Mardiati; Siregar, Gymnastiar (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2024)
This study aimed to determine the relationship between the use of cotton buds and ear complaints in Prima Indonesia University Faculty of Medicine students’ classes in 2021. The method used was analytic observational with a cross-sectional design. Data from this research analysis were obtained from questionnaires filled out by 70 students, consisting of 35 users and 35 non-users of cotton buds. Data analysis was performed using the chi-square test. The results showed a significant association between the use of cotton buds and complaints of itchy ears (p = 0.000, OR = 28.632) and ear pain (p = 0.000, OR = 2.458), but no significant association was found with hearing loss, bleeding, or ear infections. We conclude that the use of cotton buds may increase the risk of itchy and painful ear complaints.